PELAKSANAAN PERMOHONAN KASASI JAKSA PENUNTUT UMUM TERHADAP AMAR PUTUSAN BEBAS TINDAK PIDANA KORUPSI - Munir, Miftakhul (Varia Justicia, 2014)
Juridical analysis of the legal proceedings by the public prosecutor against the acquittal (vrijspraak) pursuant to Section 244 Criminal Procedure Code can be concluded that the attorney general penunutut could not bring a legal action in the form of an appeal to the Supreme Court, but there are additional guidelines implementing the Criminal Procedure Code, in item 19 on the attachment the justice minister's decision waives Section 244 Criminal Procedure Code Giving rise to various interpretations or multiple interpretations that add to the ambiguous essence of acquittal. Based on this consideration we conduct research to take the title "Implementation of Application Cassation Prosecutor Amar Verdict Against Corruption Free". The research method used in this study is the type of descriptive research by illustrating the results of the research, normative approach method, adhering to the secondary research materials that were examined directly from the results of field research (primary data), After the data collected will be analyzed the data by connecting lems problem which has been studied in order to be justified, the analysis will be conducted in which normative qualitative results will be reported in the form of a thesis. To determine the consideration of the public prosecutor in the corruption case in cassation in Magelang District Attorney is free to prove that the decision of the District Court Judge Magelang is not purely an acquittal or a verdict free from all charges (onstlag van alle rechtsvervolging) . Proved by the refutation of the verdict broke free in Magelang District Court judge. This was a key consideration Prosecutor Magelang District Attorney in an appeal against the acquittal verdict is not pure or free from any legal action as this is part of the assignment as deputy state prosecutor to satisfy the public interest (public).